Call it something else Something Else Press, Inc. 1963-1974 - Pinteño Granado, Alicia; Pineda, Mercedes (Museo Nacional Centro de Arte Reina Sofía, 2023)
The exhibition 'Call it something else: Something Else Press, Inc. (1963-1974)' focuses on the books, projects, and activities of Dick Higgins' publishing house Something Else Press, as well as on his theoretical notion of 'Intermedia', a term the publisher reappropriated to designate the heterogeneous and category-defying forms sustained by the Something Else matrix.The publishing house was founded amid the linguistic turn, a crucial moment in the arts of the 1960s, when artists began using language and text as the material of their aesthetic propositions. These projects ranging from Fluxus in the first half of the decade to Conceptual Art in the second often took the form of publications, such as books, newspapers, or magazines, which were made in explicit opposition to rarefied artworks, and aimed for wide distribution.
Impressum: This publication is edited on the occasion of the investigation "Call it something else. Something Else Press, Inc. (1963-1974)", presented in the homonymous exhibition organized by the Museo Nacional Centro de Arte Reina Sofía from September 27, 2023, to January 22, 2024
Keywords: Higgins, Dick -- 1938-1998; Something Else Press; Geschichte 1963-1974; Mixed media; Ausstellungskatalog -- Museo Nacional Centro de Arte Reina Sofía -- 27.09.2023-22.01.2024 -- Madrid